Pelatihan Produksi Foto Panorama untuk Mendukung Pembelajaran Berbasis VR Tour untuk Guru dan Dosen pada Perkumpulan Profesi Multimedia dan Teknologi Informasi (PPMULTINDO) - Sindhu Rakasiwi; Candra Irawan; Cahaya Jatmoko; Lalang Erawan; Suprayogi Suprayogi (Lembaga Pengembangan Kinerja Dosen, 2025)
The COVID-19 pandemic has triggered a transformation in online learning, requiring teachers and lecturers to adapt to educational technology, including Virtual Reality (VR) Tour. However, limited understanding and motivation are the main challenges in implementing this technology. This community service aims to provide practical training in developing VR Tour as an interactive learning media for teachers and lecturers at Rumah Diklat Indonesia. The implementation method involves an online workshop using the Zoom application, which includes a tutorial on creating 360° panoramic photos via Google Street View and processing VR Tour via the Theasys.io platform. Participants also receive technical guidance and hands-on practice sessions. The results show that participants are able to produce VR Tour content for learning, as well as improve their understanding of technology integration in education. This training equips participants with basic skills to develop virtual learning media, expand students' learning access creatively and innovatively. In conclusion, the use of VR Tour has the potential to improve the quality of distance learning, while encouraging educators to continue to adapt to technological developments in the digital era.